Patient-level factors predictive of interstitial lung disease in rheumatoid arthritis: a systematic review - Matteson, Eric; Matucci-Cerinic, Marco; Kreuter, Michael; Burmester, Gerd-Rüdiger; Dieudé, Philippe; Emery, Paul; Allanore, Yannick; Pope, Janet; Khanna, Dinesh (RMD Open, 2023)
Objective Interstitial lung disease (ILD) is an important cause of mortality in some patients with rheumatoid arthritis (RA). Patient-level factors may predict which patients with RA are at the highest risk of developing ILD and are therefore candidates for screening for this complication of the underlying disease. - Methods A systematic literature review was performed using PubMed, Embase and Scopus over a 10-year period up to July 2021. Publications reporting patient-level factors in patients with RA with and without ILD that were assessed before development of ILD (or were unchanged over time and therefore could be extrapolated to before development of ILD) were retrieved for assessment of evidence. Genetic variation in MUC5B and treatment with methotrexate were not included in the assessment of evidence because these factors have already been widely investigated for association with ILD. - Results We found consistent associations of age, sex, smoking status and autoantibodies with development of ILD. For biomarkers such as Krebs von den Lungen 6, which have been shown to be diagnostic for ILD, there were no publications meeting criteria for this study. - Conclusions This analysis provides an initial step in the identification of patient-level factors for potential development of a risk algorithm to identify patients with RA who may be candidates for screening for ILD. The findings represent a useful basis for future research leading to an improved understanding of the disease course and improved care for patients with RA at risk of development and progression of ILD.